Mesenchymal stem/stromal cells : disrupting cell therapy storage and distribution with hypothermic preservation of adipose-derived mesenchymal stromal cells - Branco, A. (2023)
Background & Aim: Cell and gene therapies (CGT) have reached new therapeutic targets but have noticeably high prices. Solutions to reduce production costs might be found in CGT storage and transportation since they typically involve cryopreservation, which is a heavily burdened process. Encapsulation at hypothermic temperatures (e.g.,2–8°C) could be a feasible alternative. In this study, we aim to determine the ability of alginate encapsulation to maintain cell viability, identity, and function in the context of MSC-based therapy manufacturing. Methods, Results & Conclusion: Adipose tissue-derived mesenchymal stromal cells (MSC(AT)) expanded using fetal bovine serum (FBS)- (MSC-FBS) or human platelet lysate (HPL)-supplemented mediums (MSC-HPL) were encapsulated in alginate beads (BeadReady™ kits kindly provided by Atelerix) for 30 min, 5 days, and 12 days. After bead release, cell recovery and viability were determined to assess encapsulation performance. MSC identity and functional immunophenotype, MSC tri-lineage differentiation potential, metabolic activity, and hematopoietic support capacity were determined and compared between timepoints. MSC(AT) were able to survive encapsulated for a standard transportation period of 5 days, with recovery values of 56 ± 5% for MSC-FBS and 77 ± 6% for MSC-HPL (which is a negligible drop compared to earlier timepoints). Importantly, MSC function did not suffer from encapsulation, with recovered cells showing robust differentiation potential, expression of immunomodulatory molecules, and hematopoietic support capacity. MSC(AT) encapsulation was proven possible for a remarkable 12 day period. There is currently no solution to completely replace cryopreservation in CGT logistics and supply chain, although encapsulation has shown potential to act as a serious competitor.